INTEGRATION OF CLINIC SERVICES TO IMPROVE PUBLIC HEALTH EFFECTIVENESS IN WYANDOTTE COUNTY PUBLIC HEALTH DEPARTMENT - Bonnelly, Cristina (My University, 2013)
Wyandotte County’s health status has been ranked the lowest of all counties in the state of Kansas. This calls for urgent action regarding its communities and population health. This county has a high population density, a high rate of unemployment and a great amount of uninsured and underserved persons, most of whom have a variety of health problems and are patients at the Wyandotte County Health Department. This and many other factors contribute to rank Wyandotte County as a very unhealthy and poor area. Some of the problems that the county is facing are: high rate of teenage pregnancies, Sexually Transmitted Diseases (STD) and Vaccine Preventable Diseases (such as pertussis). The Wyandotte County Health Department provides services such birth control, STD diagnosis, treatment and prevention, immunizations, public health education, prenatal care, family planning services and many others. The main problem that the Health Department was facing was that they were providing services in a categorical and individual way. Therefore, the Health Department’s services were not meeting the patients and the population needs. To address this problem, the Health Department had to make some changes. First, they integrated three main clinics (Family Planning Clinic, STD Clinic and Immunizations Clinic) into one clinic offering all the services. Also, they renovated the clinic area for it to be more efficient to provide the integrated services. Before and after the renovation and the integration of the services, patients and employees were given a survey about the Health Department was working. It was no surprise that in most part of the responses from both surveys, from patients and employees, they were more pleased after the integration of the services and the renovation of the area.
Keywords: Public Health; Health Department; Wyandotte County Kansas; Public Health (0573)